Collo-Diaphyseal Angle as an Optimal Anthropometric Criterion of Femur in Gender Determination - Akhlaghi, Mitra; Azizian, Abbas; Sadeghian, Mohammad Hossein; Azizian, Farhad; Zohreh Shahabi, Zohreh Shahabi; Rafiee, Shima; Mousavi, Farinaz (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: Gender determination is an important challenge in the identification of skeletal remnants and dismembered bodies. The femur bone is more likely to be preserved during accidents and over time; thus, it is one of the most useful bones in gender determination. Methods: This cross-sectional study was conducted on 54 fresh femur pairs of ˃19-year-old Iranians without anomalies or trauma. We studied the length of the femur, vertical head diameter, bicondylar width, shaft angle with the horizon, and collo-diaphyseal angle in male and female samples. Data were analyzed in SPSS using t-test and Receiver Operating Characteristic curves. P<0.05 was considered as statistically significant. Results: The samples’ mean age was 37 years in males and 41 years in females. The mean values of measurements were not significantly different between the left and right femurs (P>0.05). The vertical head diameter, maximum length, bicondylar width, and the shaft angle were significantly larger in the males, compared to females. The mean degree of collo-diaphyseal angle was significantly wider in females, compared to males (P<0.05). The highest precision of gender differentiation belonged to the collo-diaphyseal angle (96.3%) and the lowest one belonged to the vertical head diameter (77.8%). Conclusion: Based on our findings, even with the existence of only one femur bone, gender determination can be achieved with high precision. Collo-diaphyseal angle would be helpful in gender determination, even with the sole availability of the proximal part of the femur.